Assessment of Douro and Ave River (Portugal) lower basin water quality focusing on physicochemical and trace element spatiotemporal changes. Issue 12 (15th October 2018) - Couto, C. M. C. M.; Ribeiro, C.; Maia, A.; Santos, M.; Tiritan, M. E.; Ribeiro, A. R.; Pinto, E.; Almeida, A.
ABSTRACT: Water quality of Douro and Ave lower basin was evaluated regarding physicochemical parameters (pH, conductivity, dissolved oxygen and temperature), nutrient compounds (nitrates, nitrites, ammonium and orthophosphates), chlorophyll a and occurrence of trace elements (Li, Be, Al, Ti, V, Cr, Co, Ni, Cu, Zn, Se, Mo, Ag, Cd, Sb, Ba, Tl, Pb, Th and U). To study spatiotemporal variations and possible anthropogenic sources, estuarine samples were collected at nine sampling sites in Douro and five in Ave distributed along the estuaries at four sampling campaigns (spring, summer, fall and winter). According to the water quality standards for aquatic life and recreation, Douro and Ave river water quality was found out of safe limits regarding several parameters. Nitrate levels were systematically high (> 50 mg L −1 in a significant number of samples) and mean levels of trace elements were higher than the established values of Canadian Environmental Quality Guidelines for aquatic life protection for Al, Cu, Se, Ag, Cd and Pb in Douro and Ave, and also Zn in Ave. Significant spatial differences were found in Ave river estuary for trace elements with a clear trend for higher values from upstream to downstream found. Seasonal differences were also observed particularly in Douro river estuary with higher levels in spring for most elements.